Thermal Comfort and Optimum Humidity Part 1 - M. V. Jokl (Acta Polytechnica, 2002)
The hydrothermal microclimate is the main component in indoor comfort. The optimum hydrothermal level can be ensured by suitable changes in the sources of heat and water vapor within the building, changes in the environment (the interior of the building) and in the people exposed to the conditions inside the building. A change in the heat source and the source of water vapor involves improving the heat - insulating properties and the air permeability of the peripheral walls and especially of the windows. The change in the environment will bring human bodies into balance with the environment. This can be expressed in terms of an optimum or at least an acceptable globe temperature, an adequate proportion of radiant heat within the total amount of heat from the environment (defined by the difference between air and wall temperature), uniform cooling of the human body by the environment, defined a) by the acceptable temperature difference between head and ankles, b) by acceptable temperature variations during a shift (location unchanged), or during movement from one location to another without a change of clothing. Finally, a moisture balance between man and the environment is necessary (defined by acceptable relative air humidity). A change for human beings means a change of clothes which, of course, is limited by social acceptance in summer and by inconvenient heaviness in winter. The principles of optimum heating and cooling, humidification and dehumidification are presented in this paper.Hydrothermal comfort in an environment depends on heat and humidity flows (heat and water vapors), occurring in a given space in a building interior and affecting the total state of the human organism.